Oxidative potential of ambient PM2.5 in the coastal cities of the Bohai Sea, northern China: Seasonal variation and source apportionment. (May 2018) - Liu, WeiJian; Xu, YunSong; Liu, WenXin; Liu, QingYang; Yu, ShuangYu; Liu, Yang; Wang, Xin; Tao, Shu
Abstract: Emissions of air pollutants from primary and secondary sources in China are considerably higher than those in developed countries, and exposure to air pollution is main risk of public health. Identifying specific particulate matter (PM) compositions and sources are essential for policy makers to propose effective control measures for pollutant emissions. Ambient PM2.5 samples covered a whole year were collected from three coastal cities of the Bohai Sea. Oxidative potential (OP) was selected as the indicator to characterize associated PM compositions and sources most responsible for adverse impacts on human health. Positive matrix factorization (PMF) and multiple linear regression (MLR) were employed to estimate correlations of PM2.5 sources with OP. The volume- and mass-based dithiothreitol (DTTv and DTTm ) activities of PM2.5 were significantly higher in local winter or autumn ( p  < 0.01). Spatial and seasonal variations in DTTv and DTTm were much larger than mass concentrations of PM2.5, indicated specific chemical components are responsible for PM2.5 derived OP. Strong correlations ( r  > 0.700, p  < 0.01) were found between DTT activity and water-soluble organic carbon (WSOC) and some transition metals. Using PMF, source fractions of PM2.5 were resolved as secondary source, traffic source, biomass burning, sea spray and urban dust, industry, coal combustion, and mineral dust. Further quantified by MLR, coal combustion, biomass burning, secondary sources, industry, and traffic source were dominant contributors to the water-soluble DTTv activity. Our results also suggested large differences in seasonal contributions of different sources to DTTv variability. A higher contribution of DTTv was derived from coal combustion during the local heating period. Secondary sources exhibited a greater fraction of DTTv in summer, when there was stronger solar radiation. Traffic sources exhibited a prevailing contribution in summer, and industry contributed larger proportions in spring and winter. Future abatement priority of air pollution should reduce the sources contributing to OP of PM2.5 . Graphical abstract: Image 1 Highlights: DTT activity of ambient PM2.5 was measured in the coastal cities of the Bohai Sea. Seasonal and diurnal variations in PM2.5 and induced DTT activity were provided. PMF model combined with MLR apportioned main sources of PM2.5 and associated OP. DTT activity was highest as coal/biomass made significant contributions to PM2.5 mass fractions during winter. Abstract : Chemical compositions of PM2.5 regulated DTT-based OP, and the mass concentration and DTT activity of PM2.5, exhibited different emission sources characteristics.